2019
DOI: 10.1177/0284185119879686
|View full text |Cite
|
Sign up to set email alerts
|

Application of apparent diffusion coefficient values derived from diffusion-weighted imaging for assessing different sized metastatic lymph nodes in cervical cancers

Abstract: Background Lymph nodes metastasis is an important factor affecting survival rate and recurrence in cervical cancer patients. Currently, diagnosis of metastatic lymph nodes is mainly based on morphological changes on imaging. However, it is difficult to differentiate normal-sized metastatic lymph nodes with short axis of 5-10mm. Purpose To assess the diagnostic value of apparent diffusion coefficient (ADC) for discriminating different-sized metastatic lymph nodes in patients with cervical cancers. Material and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
2
6
0
1
Order By: Relevance
“…When the ADC min value of 0.72 × 10 −3 mm 2 /s was used as a cut-off value, the best validity results were obtained, with the sensitivity of 83.1%, specificity of 89.6%, and accuracy of 83.7%. These results were consistent with the previous study by Zhang et al 14 Nevertheless, using DWI alone is not accurate enough to rule in or out PLN metastases.…”
Section: Discussionsupporting
confidence: 92%
“…When the ADC min value of 0.72 × 10 −3 mm 2 /s was used as a cut-off value, the best validity results were obtained, with the sensitivity of 83.1%, specificity of 89.6%, and accuracy of 83.7%. These results were consistent with the previous study by Zhang et al 14 Nevertheless, using DWI alone is not accurate enough to rule in or out PLN metastases.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the whole-lesion ADC histogram parameters of RS-EPI DWI based on primary cervical cancer analysis performed well in identifying normal-sized LNM, and the results were similar to previous studies 6,34 based on lymph node analysis. However, our method of analyzing the primary tumor is more adaptable to clinical practice because it is difficult to preoperatively evaluate each lymph node because of the scanning thickness and the location and size of lymph nodes.…”
Section: Discussionsupporting
confidence: 84%
“…A possible explanation for this finding could be that more aggressive tumors may contain many invisible cystic and necrotic components. 30 However, Zhang et al 6 reported that ADC min had the highest value in distinguishing normal-sized LNM in cervical cancer. Although ADC min theoretically best represents the most aggressive component of a tumor, it is more susceptible to noise, artifacts, and adjacent structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-thickness cervical stromal invasion does not always signify parametrial invasion. The diagnosis of parametrial invasion requires full-thickness cervical stromal invasion and one of the following additional findings on T2WI: a speculated tumor-to-parametrial interface, a tumor nodule in the parametrium and/or tumor encasement of parametrial vessels [ 50 ].…”
Section: Discussionmentioning
confidence: 99%